2004
DOI: 10.2337/diabetes.53.5.1344
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Generates Free Radicals by an NAD(P)H, Phosphatidylinositol 3′-Kinase-Dependent Mechanism in Human Skin Fibroblasts Ex Vivo

Abstract: Oxidative stress may be involved in the development of vascular complications associated with diabetes; however, the molecular mechanism responsible for increased production of free radicals in diabetes remains uncertain. Therefore, we examined whether acute hyperinsulinemia increases the production of free radicals and whether this condition affects proliferative extracellular signal؊regulated kinase (ERK-1 and -2) signaling in human fibroblasts in vitro. Insulin treatment significantly increased intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 41 publications
3
52
0
2
Order By: Relevance
“…Similarly, in skin fibroblasts, Ceolotto et al (114) found that insulin-stimulated ROS production was also dependent on PI 3Ј-kinase activity. In contrast, we reported that insulin-stimulated ROS generation in 3T3-L1 adipocytes, presumably via a Nox4-mediated pathway, was not sensitive to PI 3Ј-kinase inhibition (26).…”
Section: Generation Of H 2 O 2 By Cellular Insulin Stimulationmentioning
confidence: 99%
“…Similarly, in skin fibroblasts, Ceolotto et al (114) found that insulin-stimulated ROS production was also dependent on PI 3Ј-kinase activity. In contrast, we reported that insulin-stimulated ROS generation in 3T3-L1 adipocytes, presumably via a Nox4-mediated pathway, was not sensitive to PI 3Ј-kinase inhibition (26).…”
Section: Generation Of H 2 O 2 By Cellular Insulin Stimulationmentioning
confidence: 99%
“…In response to dietary challenges, adipocytes and endothelial cells activate classical inflammatory pathways, which impair the metabolic action of insulin, paving the way to diabetes [3]. In turn, hyperglycemia and hyperinsulinemia elicit multiple pro-inflammatory responses [4][5][6]. This is reflected by mild elevation of inflammatory markers in patients with diabetes or the metabolic syndrome [7].…”
Section: Introductionmentioning
confidence: 99%
“…In skin treated with LPS, NADPH oxidase in infiltrating neutrophils is well known to produce a large amount of superoxide anion (9) as it does in other organs. Although NADPH oxidase in the nonphagocytic cells has been less well characterized, a physiologically relevant low level of generation of free radical and neutrophil-like expression of NADPH oxidase subunits is also present in skin keratinocytes (10,11) and fibroblasts (12). However, there was a significant increase in the lipid radicals from the skin of mice treated with LPS for 6 h, even in gp91 phox knockout animals.…”
Section: Discussionmentioning
confidence: 78%
“…It is also present in keratinocytes (10,11) and fibroblasts (12). XO is activated in 12-O-tetradecanoyl-13-phorbol acetate-treated murine skin (13) and in human skin keratinocyte cells irradiated with UV B (14).…”
Section: Ipopolysaccharide (Lps) An Outer-membrane Component Ofmentioning
confidence: 99%